1999
DOI: 10.1185/03007999909114094
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Fixed Combination Phytomedicine in the Treatment of the Common Cold (Acute Viral Respiratory Tract Infection): Results of a Randomised, Double Blind, Placebo Controlled, Multicentre Study

Abstract: This study shows that the herbal remedy is effective and safe. The therapeutic benefit consists of a rapid onset of improvement of cold symptoms. If patients with colds are able to start the application of the herbal remedy as soon as practical after the occurrence of the initial symptoms, the benefit would be expected to increase (e.g. self-medication).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 14 publications
3
32
0
Order By: Relevance
“…Echinacea was selected as the active treatment because its popularity and name recognition provided reasonable potential of expectancyrelated placebo effects. At the time the current study was designed, several published trials of echinacea had reported benefi t, [37][38][39][40] whereas one, our own, 41 had not. The study design reported here provided the advantage of being able to test for specifi c effects of echinacea in addition to the main focus on effects related to placebo and expectancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinacea was selected as the active treatment because its popularity and name recognition provided reasonable potential of expectancyrelated placebo effects. At the time the current study was designed, several published trials of echinacea had reported benefi t, [37][38][39][40] whereas one, our own, 41 had not. The study design reported here provided the advantage of being able to test for specifi c effects of echinacea in addition to the main focus on effects related to placebo and expectancy.…”
Section: Methodsmentioning
confidence: 99%
“…In 2002, when we designed this trial, nearly all published echinacea trials had reported benefi t, [37][38][39][40] and societal expectations were high. Then came 4 highly publicized negative echinacea trials, our own in Medicine (2005).…”
Section: Pl Ac Eb O Ef Fec T S a Nd T He Co M M On Col Dmentioning
confidence: 99%
“…However, Schoneberger,33 in an 8-week trial, noted a shorter duration of illness and a trend toward fewer study participants with infection, indicating a possible preven- tive effect. In other placebo-controlled trials, Schmidt and colleagues 34 found a 15% lower frequency of infection in subjects given echinacea (P = .08), Forth and Beuscher 35 reported a relative risk reduction of 38% in nasal symptoms (P<.005), and Henneicke-von Zepelin et al 36 reported a superiority of echinacea preparation over placebo in the treatment of the common cold. On the other hand, Turner et al 37 found no significant difference in the occurrence of infection or severity of illness in a group of 92 volunteers challenged with rhinovirus type 23 and treated with echinacea for 5 days compared with control subjects.…”
Section: Commentmentioning
confidence: 99%
“…data]. The most recent research focused on the efficacy of Esberitox N in the therapy of acute viral respiratory tract infection [22, 28]. Some papers on clinical studies are discussing the efficacy of the remedy as adjuvant drug in antibiotic therapy of bacterial infections [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…These considerations led to the idea of combining antibiotic treatment with an allopathic phyto-immunomodulator (Esberitox ® N), which is registered in Germany for several indications such as the supportive therapy of severe bacterial infections treated with antibiotics or treatment of the common cold and plays an important role in the treatment of patients in the general practice [20, 21, 22]. Esberitox N contains an extract of the herbal drugs, Echinacea, Baptisia and Thuja (cone flower, wild indigo and white cedar).…”
Section: Introductionmentioning
confidence: 99%